2021
DOI: 10.1021/acs.chemrev.1c00558
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Halogen-Atom Transfer (XAT) for the Generation of Carbon Radicals in Synthetic Photochemistry and Photocatalysis

Abstract: The halogen-atom transfer (XAT) is one of the most important and applied processes for the generation of carbon radicals in synthetic chemistry. In this review, we summarize and highlight the most important aspects associated with XAT and the impact it has had on photochemistry and photocatalysis. The organization of the material starts with the analysis of the most important mechanistic aspects and then follows a subdivision based on the nature of the reagents used in the halogen abstraction. This review aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
259
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 338 publications
(263 citation statements)
references
References 602 publications
3
259
0
1
Order By: Relevance
“…However, >95% recovery of the starting materials 2l and 2m was observed with full decomposition of the diazonium salts under current reaction conditions (Fig 8). Since the in halogen-atom transfer (XAT) of different alkyl halides can be varied according to the bond dissociation energy (BDE) 1 . As a result, the relative rates for halogen atom abstractions was determined by the strength of the C−halogen bonds, and the result of our experiments also support that the trend of halogen atom abstractions is iodides > bromides > chlorides 1,65,66 .…”
Section: Mechanistic Studymentioning
confidence: 99%
See 3 more Smart Citations
“…However, >95% recovery of the starting materials 2l and 2m was observed with full decomposition of the diazonium salts under current reaction conditions (Fig 8). Since the in halogen-atom transfer (XAT) of different alkyl halides can be varied according to the bond dissociation energy (BDE) 1 . As a result, the relative rates for halogen atom abstractions was determined by the strength of the C−halogen bonds, and the result of our experiments also support that the trend of halogen atom abstractions is iodides > bromides > chlorides 1,65,66 .…”
Section: Mechanistic Studymentioning
confidence: 99%
“…Carbon radical has been well recognized as an easily-generated, reactive, and variable species in organic synthesis 1 . As a result, numbers of critical transformations via radical process provide wonderfully alternative methods to address the shortcomings in ionic chemistry which one pair of electrons are involved in 1 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…recently reported that α-aminoalkyl radical, generated via SET between alkyl amines and a close shell excited PC*, can initiate halogen atom transfer (XAT) (Figure 1a, right). 16,17 Therefore, the concept of super photoreducing radicals in conPET systems is weakened due to the common usage of amine as the sacrificial electron donor. Furthermore, a recent study by Nocera and colleagues questioned the viability for radicals generated in-situ during conPET or electrophotocatalysis to act as efficient photocatalysts, due to their short-lived excited state which should hamper their participation in bimolecular reactions with substrates.…”
Section: Introductionmentioning
confidence: 99%